2007
DOI: 10.1074/jbc.m608942200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assembly of TRPC1-STIM1-Orai1 Ternary Complex Is Involved in Store-operated Calcium Influx

Abstract: Store-operated calcium entry (SOCE) is a ubiquitous mechanism that is mediated by distinct SOC channels, ranging from the highly selective calcium release-activated Ca 2؉ (CRAC) channel in rat basophilic leukemia and other hematopoietic cells to relatively Ca 2؉ -selective or non-selective SOC channels in other cells. Although the exact composition of these channels is not yet established, TRPC1 contributes to SOC channels and regulation of physiological function of a variety of cell types. Recently, Orai1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
187
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(197 citation statements)
references
References 44 publications
9
187
1
Order By: Relevance
“…There is now considerable evidence for store-operated or capacitative Ca 2ϩ entry in different smooth muscle types. The presence of store-operated Ca 2ϩ influx pathways has been demonstrated previously in guinea pig, rat, human, and porcine airway smooth muscle (6,34,35,48,58). Previous studies from our group have established that SOCE exists in human ASM (6,58).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…There is now considerable evidence for store-operated or capacitative Ca 2ϩ entry in different smooth muscle types. The presence of store-operated Ca 2ϩ influx pathways has been demonstrated previously in guinea pig, rat, human, and porcine airway smooth muscle (6,34,35,48,58). Previous studies from our group have established that SOCE exists in human ASM (6,58).…”
Section: Discussionmentioning
confidence: 64%
“…However, this does not rule out CD38 regulation of TRPC3 channels per se. This may occur within caveolae expressing CD38 and TRPC3, via direct complexing of CD38 and TRPC3, or through modulation of the recently recognized trigger for SOCE, stromal interaction molecule (STIM1) (34,36,40). Our additional studies showing partial blockade of SOCE (or of TNF␣ and CD38 overexpression effects) by 8-Br-cADPR suggest that at least some of the CD38 effects may be mediated via cADPR (which is produced by CD38 activation following agonist exposure).…”
Section: Discussionmentioning
confidence: 68%
“…For the shOrai1, the sense sequence was 5Ј-CACCTCACTGGT-TAGCCATAAGACGAATCTTATGGCTAACCAGTGA-3Ј, and the antisense sequence was 5Ј-AAAACCTTTACACGCTAGATGGTttcgTCTTATGGCTAACCAGTGA-3Ј. These sequences were synthesized and hybridized as previously described (33,34). Plasmids were used for silencing experiments at 1 g/l.…”
Section: Methodsmentioning
confidence: 99%
“…It is now clear that Orai1 [4][5][6][7]9,[33][34][35], and perhaps Orai2 and Orai3 [34,36] are the proteins that mediate I crac . However, recently it was shown that Orai1 forms a complex with STIM1 and TRPC1 [37]. Of particular significance is the finding that KD of TRPC1 partially inhibited SOCs-mediated Ca 2+ influx and I soc , whereas KD of Orai1 completely inhibited Ca 2+ influx and I soc [37].…”
Section: Trpc Channels As Socsmentioning
confidence: 99%